Comparative Study of the Inhibition of E. coli and Murine Aspartate Transcarbamylase by Phenobarbital Analogues - Balbaa, Mahmoud; Hammoud, Razan; Yusef, Hoda (Letters in Drug Design & Discovery, 2016)
Introduction: Aspartate transcarbamylase (ATCase) is involved in the initial steps of pyrimidine nucleotide biosynthesis and subject to regulation. Objective: Since Phenobarbital is an important drug, the current study focuses on a comparative investigation of the inhibition of bacterial and murine ATCase by some phenobarbital analogues. Methods: Phenobarbital analogues (thymidine, phenobarbital, and thiobarbituric acid) have been subjected for in vitro and in vivo investigation of their effect on ATCase in mice and three strains of Escherichia coli. Results: The half maximal inhibitory concentrations (IC50) of ATCase activity were measured for each compound. According to IC50 values, an in vitro and in vivo inhibition was obtained upon the treatment of mammalian and bacterial ATCases with the three compounds, whereas thiobarbituric acid is the most potent among all. Its obtained IC50 values are 0.2 ± 0.045 and 0.3 ± 0.03 mM for the bacterial and mammalian enzyme, respectively. Furthermore, the in vivo treatment of ATCase with different doses of these compounds showed the same tendency in a dose-dependent manner. Conclusion: These observations suggest that these inhibitors may interfere with the regulation of the enzyme and eventually lead to an additional biological effect of phenobarbital analogues in mammals and bacteria.
Keywords: thymidine